Investigation of Chromosomal Structural Abnormalities in Patients With Undiagnosed Neurodevelopmental Disorders - Cao, Ye; Luk, Ho Ming; Zhang, Yanyan; Chau, Matthew Hoi Kin; Xue, Shuwen; Cheng, Shirley S. W.; Li, Albert Martin; Chong, Josephine S. C.; Leung, Tak Yeung; Dong, Zirui; Choy, Kwong Wai; Lo, Ivan Fai Man (Frontiers in Genetics, 2022)
Background: Structural variations (SVs) are various types of the genomic rearrangements encompassing at least 50 nucleotides. These include unbalanced gains or losses of DNA segments (copy number changes, CNVs), balanced rearrangement (such as inversion or translocations), and complex combinations of several distinct rearrangements. SVs are known to play a significant role in contributing human genomic disorders by disrupting the protein-coding genes or the interaction(s) with cis-regulatory elements. Recently, different types of genome sequencing based tests have been introduced in detecting various types of SVs other than CNVs and regions with absence of heterozygosity (AOH) with clinical significance. Method: In this study we applied mate-pair low pass (~4X) genome sequencing with large DNA-insert (~5kb) in a cohort of 100 patients with neurodevelopmental disorders who did not receive informative results from routine CNV investigation. Read-depth based CNV analysis and chimeric-read-pairs analysis were used for CNVs and SVs analysis. Region of AOH was indicated by a simultaneous decrease in the rate of heterozygous SNVs and increase in the rate of homozygous SNVs. Results: Firstly, we re-examined the 25 previously reported CNVs among 24 cases in this cohort. The boundaries of these twenty-five CNVs including 15 duplications and 10 deletions detected were consistent with the ones indicated by chimeric-read-pairs analysis while the location and orientation were determined in 80% of duplications (12/15). Particularly, one duplication was involved in complex rearrangements. In addition, among all the 100 cases, 10% of them were detected with rare or complex SVs (>10Kb) and 3% were with multiple AOH (>=5Mb) locating in imprinting chromosomes identified. In particular, one patient with overall of 214.5Mb of AOH identified on 13 autosomal chromosomes suspected parental consanguinity. Conclusion: In this study, mate-pair low-pass GS resolved a significant proportion of CNVs with inconclusive significance, and detected additional SVs and regions of AOH in patients with undiagnostic neurodevelopmental disorders. This approach complements first-tier CNV analysis for NDDs not only through increasing the resolution of CNVs detection but also enhance the characterization of SV and discovery of potential causative regions (or genes) contributory to DD/ID.